(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
This paper addresses public institutions’ logistical challenges, focusing on project tracking and transparency. One challenging aspect of this endeavor is maintaining a clear and transparent record of ongoing projects while ensuring effective communication with all relevant stakeholders. Using machine learning and a comprehensive set of tools (to eliminate repetitive, time-consuming tasks), institutions can more efficiently manage and track projects with reduced manpower and fewer resources.